A comparison between two different definitions of contrast-induced acute kidney injury in patients with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention. (1st May 2016) - Centola, Marco; Lucreziotti, Stefano; Salerno-Uriarte, Diego; Sponzilli, Carlo; Ferrante, Giulia; Acquaviva, Roberta; Castini, Diego; Spina, Marianna; Lombardi, Federico; Cozzolino, Mario; Carugo, Stefano
Abstract: Background: Contrast-induced acute kidney injury (CI-AKI) is associated with significantly increased mortality after primary percutaneous coronary intervention (pPCI) for ST-segment elevation myocardial infarction (STEMI). The prognostic value of CI-AKI depends on the definitions used to define it. We compare the predictive accuracy of long-term mortality of two definitions of CI-AKI on consecutive patients undergoing pPCI for STEMI. Methods: Incidence, risk factors and long-term prognosis of CI-AKI were assessed according to two different definitions: the first as an increase in serum creatinine ≥ 25% or ≥ 0.5 mg/dl from baseline within 72 h after pPCI (contrast-induced nephropathy (CIN) criteria), the second one according to Acute Kidney Injury Network (AKIN) classification system. Results: A total of 402 patients were enrolled. The median follow-up period was 12 ± 4 months. Long-term mortality rate was 9.5%. Independent predictors of long-term mortality were: older age, basal renal impairment, left ventricular ejection fraction < 40%, in-hospital major bleedings and CI-AKI. A significant correlation was found between mortality and CI-AKI as assessed by both CIN (HR 4.84, 95% CI: 2.56–9.16, p = 0.000) and AKIN (HR 9.70, 95% CI: 5.12–18.37, p = 0.000) definitions. The area under the receiver operating curve was significantly larger for predicting mortality with AKIN classification than with CIN criteria (0.7984 versus 0.7759; p = 0.0331). Conclusions: In patients with STEMI treated by pPCI, CI-AKI is a frequent complication irrespective of the criteria used for its definition. AKIN, however, seems to provide a better accuracy in predicting long-term mortality than CIN criteria.